2018
DOI: 10.3389/fendo.2018.00418
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Modulates Podocyte Glucose Transport

Abstract: Podocytes play a central role in the maintenance of the glomerular filtration barrier and are cellular targets of angiotensin II (AngII). Non-hemodynamic pathways of AngII signaling regulate cellular function and mediate podocyte abnormalities that are associated with various glomerulopathies, including diabetic kidney disease. In this study we investigated the capacity of AngII to modulate glucose uptake in mouse podocytes expressing the human AT1 receptor (AT1R+) after 5 days of exposure to normal (NG, 5.6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Relevant studies have shown that GLUTs play a key role in the glucose uptake of astrocytes 30 , among which GLUT1, GLUT3, and GLUT4 play important roles 31 . Hence, in the current study, we detected the expression levels of GLUT1, GLUT3, and GLUT4 induced by ketamine in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that GLUTs play a key role in the glucose uptake of astrocytes 30 , among which GLUT1, GLUT3, and GLUT4 play important roles 31 . Hence, in the current study, we detected the expression levels of GLUT1, GLUT3, and GLUT4 induced by ketamine in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As Glut1 predominates in mesangial cells, as well as in podocytes, Glut1 activity alterations are deleterious in diabetic nephropathy, stimulating renal extracellular matrix production the most [ 87 , 88 ]. The GLUT1 Enh2 genetic variation, located within a binding site for the insulin-responsive transcription factor, is associated with albuminuria, matrix expansion and glomerulosclerosis [ 88 ].…”
Section: Glut1 Inhibition In Other Settingsmentioning
confidence: 99%
“…The GLUT1 Enh2 genetic variation, located within a binding site for the insulin-responsive transcription factor, is associated with albuminuria, matrix expansion and glomerulosclerosis [ 88 ]. Podocytes enhance their glucose uptake but decrease their GLUT1 expression when exposed to mechanical stress, suggesting alternative glucose transporters during stress/injury [ 87 , 89 ].…”
Section: Glut1 Inhibition In Other Settingsmentioning
confidence: 99%
“…GLUT4 is expressed in the glomerulus [27], and in the mesangial cells and podocytes. Animal studies indicate that GLUT1, GLUT2, and GLUT4 expression in podocytes is modulated by angiotensin II [28]. The presence of the GLUT4 mRNA and protein were detected in the thick ascending limb of the loop of Henle (TAL), and it has been suggested that GLUT4 may be involved in managing the local resources in this segment [24].…”
Section: Human Renal Glut Proteinsmentioning
confidence: 99%